(untitled) (PAAN Journal, 2025)
This paper examines the effectiveness of accountability mechanisms within the local governments of Nepal, with a primary focus on evaluating their influence on governance and the delivery of public services. Employing a descriptive analysis, the study analyzes various accountability structures such as the municipal executive committee, the council, the monitoring committee, the legal committee, etc. It investigates the implementation and execution of these mechanisms and assesses their outcomes. Through case studies and situational analyses, the research highlights the strengths and weaknesses inherent in these systems, pinpointing key factors that either contribute to or impede their success. The findings contribute valuable insights to the ongoing discourse surrounding the enhancement of local governance in Nepal, providing actionable recommendations for policymakers and stakeholders to bolster accountability practices and foster improved public administration at the grassroots level of the country.